The Right to Manage Coastal Tourism to Support Indigenous People's Income in the Perspective of Coastal Community Welfare - Saija, Ronald; Pariela, Marselo Valentino Geovani; Sihite, Sri Rumada (Batulis Civil Law Review, 2024)
Introduction: The right to manage coastal tourism to support the customary income of the land of West Seram Regency from the perspective of the welfare of coastal communities, where it can be said that tourism management is one of the efforts made by the community and government to preserve tourist attractions.Purposes of the Research: The tourism management responsibilities that are interesting to carry out research, especially the tourism management of Negeri Eti in the Baray part of Seram Regency and providing management obligations to the Negeri Eti community in the West Seram Regency as well as research related to the welfare allocation or it could be said to be the results of the allocation of customary land to be managed for beach tourism.Methods of the Research: The research method used is in accordance with the research objectives where the type of research used is sociolegal (sosiolegal research) namely a research method combining doctrinal legal research and empirical legal research methods.Results of the Research: The results of this research show that developing tourism potential in an area requires information, physical factors and a good coastal environment which includes accessibility, supporting facilities and infrastructure. There is Village Regulation Number 1 of 2022 concerning Management of Land, Coastal and Marine Natural Resources. Eti Village, West Seram District, Maluku Province, can be implemented by Eti Village to provide welfare for coastal indigenous communities in the future.